2004
DOI: 10.1080/13576280400002585
|View full text |Cite
|
Sign up to set email alerts
|

Students, Stress and Coping Strategies: A Case of Pakistani Medical School

Abstract: The prevalence of perceived stress seems to be high among medical students, which tends to affect not only their academic performances but also all aspects of health. Review of academics and exam schedules, more leisure time activities, better interaction with the faculty and proper guidance, advisory services and peer counselling at the campus could do a lot to reduce the stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
240
18
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(306 citation statements)
references
References 9 publications
32
240
18
16
Order By: Relevance
“…Recent studies in Sweden and in Pakistan showed similar results in terms of overall gender differences. 7,16 However, a study conducted in Egypt on 288 undergraduate medical students reported no gender differences for stress. 17 Stressors identified in our study included academic curriculum workload issues, personal problems, communication and/or language difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies in Sweden and in Pakistan showed similar results in terms of overall gender differences. 7,16 However, a study conducted in Egypt on 288 undergraduate medical students reported no gender differences for stress. 17 Stressors identified in our study included academic curriculum workload issues, personal problems, communication and/or language difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…12 Language and communication difficulties were cited by only two students in our study, one of whom was a returning student who had completed the first four years of training in Cuba in terms of Students in our study used similar coping strategies to those in other studies. 6,7,19,21 These included lifestyle changes, and/or constructive engagement with support structures within and outside the family system. Female students in our study favoured both methods generally, more so than their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the consequences of maladaptive coping may lead to decreased self-esteem, increased alcohol consumption and smoking, reduced functioning of the immune system 26 , increased suicidal tendencies, poor academic performance and drop outs 27 . A study done in a medical school in Pakistan indicated that most students presented with symptoms of low moods, inability to concentrate, short temper, change in sleep patterns and loneliness and others presented with headaches and stomach-aches 28 . In a local study done in Pretoria 6 students reported the use of medication to alleviate their depression, regardless of whether a prescription was obtained.…”
Section: Lazarus and Folkmanmentioning
confidence: 99%